Population Analysis of some of Turkish and Iranian Parthenogenetic Artemia using Biometric Components - Ramin Manaffar; Razieh Abdilzadeh; Tahereh Akbarialmajough; Armin Eskandari; Soheila Ebrahimi; Yasemin Saygi (تاکسونومی و بیوسیستماتیک, 2018)
Abstract Artemia, small crustacean, not only is very useful in aquaculture industry but also is a model organism for biologists. The parthenogenetic population of Artemia has not been classified so far mainly because of high dispersal, different ploidy levels and diverse physiological and morphometric characteristics. Due to the importance of the morphometric traits in taxonomy of Artemia, in this study morphometric characters of 11 Artemia populations, comprising 7 parthenogenetic Artemia populations from Turkey and 4 populations from Iran were studied. Most of Turkey populations were studied for the first time in the world. In this regard, eleven morphometric parameters of laboratory cultured Artemia were compared. The results showed that the characteristics such as the compound eyes, abdominal length, head width, Telson length and the number of left and right thorns could play an important role in the separation of populations. This study revealed that some morphometric characters of Artemia Can be of high significance for morphometric studies of Artemia. Based on DA (Discriminant Analysis), using some morphometric traits of Artemia, the studied parthenogenetic Artemia can be classified into three groups.